Improved performance indicators and institutional setup for more viable compost production from municipal solid waste in Sri Lanka - Manipura, A.; Drechsel, Pay; Jayawardhana, H. M. L. C.; Shanmugapriya, R.; Mannapperuma, N. R.; Jayatilleke, H. S. I. (Elsevier, 2025)
Managing municipal solid waste (MSW) is challenging for most local authorities (LAs), especially in urban and peri-urban areas due to increasing waste quantities and decreasing options for safe disposal. Many LAs around the world prefer composting organic waste as a means of waste volume (and transport cost) reduction and cost recovery option within a circular economy framework. To optimize compost production with a focus on cost recovery, a systematic study was conducted at 22 composting stations located in Sri Lanka’s highly populated Western Province. The study examined process management from organic waste collection to product quality and cost recovery via compost sales. Collected organic waste conversion into compost was varied between 1 % and 15 % and time taken for completion of the process varied between 2.5 – 4.5 months. No standard operating procedure was observed though input organic matter was of similar nature. Excess leachate and odour production reported by 59 % of the surveyed stations. Complete analysis of compost quality was hardly reported by any LAs and no sales and marketing strategies were adopted to boost the cost recovery. Poor data management has hindered the identification of improvement opportunities and performance benchmarking of composting stations run by LAs. To address these significant performance variations observed among the stations, a monitoring and evaluation framework is proposed based on four composite key performance indicators (KPIs): General Facility Management Index (GFMI), Composting Process Management Index (CPMI), Compost Quality Index (CQI), and Cost Recovery Index (CRI). These KPIs serve to benchmark performance and identify incremental improvement opportunities at each station. However, to address institutional and human capacity challenges an institutional partnership model is also proposed, which could incentivize the implementation and achievements of the KPIs while reducing the pressure on LAs to reach the compost market.